Shared Transcriptional Machinery at Homologous Alleles Leads to Reduced Transcription in Early Drosophila Embryos - Deng, Hao; Lim, Bomyi (Frontiers in Cell and Developmental Biology, 2022)
The mechanism by which transcriptional machinery is recruited to enhancers and promoters to regulate gene expression is one of the most challenging and extensively studied questions in modern biology. We explored the possibility that interallelic interactions between two homologous alleles might affect gene regulation. Using an MS2- and PP7-based, allele-specific live imaging assay, we visualized de novo transcripts of a reporter gene in hemizygous and homozygous Drosophila embryos. Surprisingly, each homozygous allele produced fewer RNAs than the corresponding hemizygous allele, suggesting the possibility of allelic competition in homozygotes. However, the competition was not observed when the enhancer-promoter interaction was weakened by placing the reporter construct in a different chromosome location or by moving the enhancer further away from the promoter. Moreover, the reporter gene showed reduced transcriptional activity when a partial transcription unit (either an enhancer or reporter gene only) was in the homologous position. We propose that the transcriptional machinery that binds both the enhancer and promoter regions, such as RNA Pol II or preinitiation complexes, may be responsible for the allelic competition. We showed that the degree of allelic interference increased over developmental time as more Pol II was needed to activate zygotic genes. Such allelic competition was observed for an endogenous gene as well. Our study provides new insights into the role of 3D interallelic interactions in gene regulation.